Skenario Perencanaan Pembangunan Pariwisata Kabupaten Kutai Kartanegara - Muhammad Amin (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2018)
This research was conducted with the understanding, describe and explain the stages of preparation of tourism development planning implemented by the Department of Tourism with using the scenario of planning and the stages of determination implemented by the Department of Culture and Tourism and Regional Development Planning Kutai KartanegaraThis research uses qualitative with descriptive approach. Data collection was done by using interview technique, observation and documentation. The validity of the data is based on fourth criteria: (1) Credibility, (2) Tiltiness, (3) Dependency, and (4) Certainty. While the process of data analysis using technical analysis of interactive data model from Miles and Hubberman.The results showed that at the stage of preparation in the planning of tourism development using scenario planning focuses on tracking, analizing, imaging and deciding so that it has shown the stages of the process against the preparation of tourism development planning. More, at the stage of determining the scenario planning of tourism development Ripparkab become master plan of tourism development. Department of Tourism became the main OPD and supported by several OPD related in the process of tourism development so that tourism development planning run in integrity.The suggestion refer to the results of research that has been elaborated. The implementation of tourism development should be more equitable not focusing on urban areas and implementing event-based tourism, the government is also more trying to attract investors to invest in Kutai Kartanegara regency so as not to burden the budget sector and can provide a good economic impact to the community around the object and influence on Local revenue in the tourism sector. Department of Tourism more synergy to OPD support for tourism development in Kutai Kartanegara so that the development of tourism sector can maximum running.Keywords: Tourism, Scenario Planning, and Development Planning